2000
DOI: 10.1177/0003489400109s1206
|View full text |Cite
|
Sign up to set email alerts
|

New Clarion Electrode with Positioner: Insertion Studies

Abstract: A new straight thin electrode array (universal electrode) was designed to be used together with a positioner, which will place the electrode array at the medial wall (modiolus) of the cochlea. The study objectives were to demonstrate safety and ease of insertion, tissue trauma, electrode position, and depth for universal and standard electrodes in human temporal bones; to test functional properties in cats; and to determine the surgical procedure and electrophysiological benefits in a clinical study. The cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Synthetic models of the ST have been used for the purpose of insertion force measurement during cochlear implantation [4], [5], [7]. Existing studies have shown the importance of quantifying force components and the assessment of electrode trajectories for specific electrode designs, for the minimization of trauma [4], [5], [8]- [17], optimal electrode placement [1], [4], [9], [13], [14], [18]- [21], and to avoid damage to the electrode [8], [11], [12]. In this paper, we examine and compare 0018-9294/$25.00 © 2007 IEEE force delivery, electrode positions and surgical techniques for implants not previously considered: the Contour and Contour Advance electrodes.…”
Section: A Measurement Of Insertion Forcesmentioning
confidence: 99%
“…Synthetic models of the ST have been used for the purpose of insertion force measurement during cochlear implantation [4], [5], [7]. Existing studies have shown the importance of quantifying force components and the assessment of electrode trajectories for specific electrode designs, for the minimization of trauma [4], [5], [8]- [17], optimal electrode placement [1], [4], [9], [13], [14], [18]- [21], and to avoid damage to the electrode [8], [11], [12]. In this paper, we examine and compare 0018-9294/$25.00 © 2007 IEEE force delivery, electrode positions and surgical techniques for implants not previously considered: the Contour and Contour Advance electrodes.…”
Section: A Measurement Of Insertion Forcesmentioning
confidence: 99%
“…The stylet is retracted after, or during, insertion of the electrode allowing the electrode to return to its molded spiral shape and assume a final position closer to the modiolus. Two versions of the HiFocuse electrode design use a separate space-filling positioner to move the active electrode closer to the modiolus (Lenarz et al, 2000). In the first clinical version of this electrode, the HiFocus Ie, the positioner is inserted after full insertion of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In the Clarion HiFocus II electrode, a positioner is inserted into the cochlea after placement of the implant. The positioner is placed between the implant and the lateral cochlea wall, and pushes the electrode array towards the modiolus [1,2,4,7,8]. An alternative mechanism is implemented in the Nucleus CI24R(CS) Contour electrode.…”
Section: Introductionmentioning
confidence: 99%